PIRANTI LUNAK UNTUK MENDESAIN PROGRAM DALAM BAHASA PEMROGRAMAN C BERDASARKAN HOARE LOGIC - Arnold Aribowo; Pujianto Yugopuspito; Julian Fetriandhy Altanijah (Jurusan Teknik Informatika, 2010)
The purpose of Hoare Logic is to provide a set of logical rules in order to reason about the correctness of computer programs with the rigor of mathematical logic. Because of that, Hoare Logic becomes the axiomatic basis for computer programming with several rules to prove the correctness of program. Hence, we can apply the proven rules of Hoare Logic as the basis to design a program correctly according to Hoare Logic. In this paper, Hoare Logic is applied in a software which is designed to help the user to design a program in C programming language correctly based on rules in Hoare Logic. When using this software, the user needs to know what program he will create and analyze an algorithm for it. After that, the user can use the software containing the rules of Hoare Logic and write the pseudo-code of C to design his program. At the end of this application, the user will obtain a source code of the program written in C programming language. This software is guaranteed to produce 100% correct output only if the users have the basic understanding of Hoare Logic as well as C program language before using this software.